2000
DOI: 10.1080/028418500127345587
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging in clinically suspected acute cholecystitis: A comparison with ultrasonography

Abstract: MR has a higher sensitivity than US for diagnosing acute cholecystitis and, with increased accessibility, may be the first imaging method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…Both conventional magnetic resonance imaging (MRI) [22-24] and magnetic resonance cholangiopancreatography [23,24] have been evaluated in the diagnosis of acute calculous cholecystitis and its complications [25]. When compared to ultrasonography, some have found MRI to be equivalent [26] and some have found it to be superior [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both conventional magnetic resonance imaging (MRI) [22-24] and magnetic resonance cholangiopancreatography [23,24] have been evaluated in the diagnosis of acute calculous cholecystitis and its complications [25]. When compared to ultrasonography, some have found MRI to be equivalent [26] and some have found it to be superior [27].…”
Section: Resultsmentioning
confidence: 99%
“…Acute cholecystitis accounts for 3–10% of all patients with abdominal pain and is the most common cause of acute abdominal pain in the right upper quadrant, especially in the elderly patients [25]. Sonography is still used as the initial imaging technique for evaluating patients with suspected gallbladder (GB) disease because of its high sensitivity at the detection of GB stones, its real-time character, and its speed and portability [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the sensitivity of DWIBS/ T2 in the diagnosis of acute cholecystitis was 90.9%. Similarly, previous results have indicated that DWIBS/T2 is superior to US and CT as a diagnostic tool (27,28), possibly due to the distinct contrast between high signal intensity regions and surrounding tissues detected by DWIBS/T2, which makes diagnosis more accurate. Indeed, contrast agents are considered to be useful in the diagnosis of biliary diseases (29).…”
Section: Discussionmentioning
confidence: 94%
“…Modern MR systems with fast pulse sequences acquired during breath‐hold give excellent images for visualisation of the biliary tree and liver parenchyma. Especially, T2W HASTE sequences without and with fat saturation have shown a high sensitivity to demonstrate oedema and fluid which is of great value in diagnosing inflammatory conditions (4, 7, 9, 10). These pulse sequences also give excellent image quality in uncooperative patients.…”
Section: Discussionmentioning
confidence: 99%